Design Synthesis for Swept-Wing Combat Aircraft Incorporating Stealth Technology - Siegers, F. (Cranfield University, 1994)
The College of Aeronautics has been involved in several research contracts funded by the Defence Research Agency of the United Kingdom to investigate the design synthesis and optimization of Military aircraft. This report presents the results of the latest such investigation into the enhancement of a swept-wing combat aircraft design synthesis to incorporate stealth technology. In the light of the current changes in the method of procurement of airborne weapons systems it has become necessary to develop combat aircraft which are effective against a wide range of threats whilst meeting the requirements of both navy and air force. One way of doing this is to incorporate into combat aircraft those features which make it stealthy, in other words reducing their detectability by means of radar, infrared, visual and acoustics identification methods. Although the full benefits of stealthy aircraft may only become apparent when such systems are deployed within appropriate strategic and tactical environment, it is important to define the features inherent to the aircraft at the conceptual design stage. This report briefly describes those features of stealthy aircraft incorporated into the design synthesis, leading to the definition of a baseline aircraft, followed by a full description of the design synthesis methodology. Finally, the development of the design synthesis computer code is outlined, rounded off by plans for future work.